Proceedings of the 2nd International Food Research Conference - Faculty of Food Science and Technology (Faculty of Food Science and Technology, 2019)
The 2nd International Food Research Conference, held in 2019 and organized by the Faculty of Food Science and Technology, focused on the theme Bridging the Gap, Transforming the Future.